Consultant Pharmacist-Provider Collaboration in U.S. Assisted Living Facilities: A Pilot Study - Kenneth C. Hohmeier; Kelsey D. Frederick; Krishna Patel; Kristi Summers; Morgan Honeycutt (MDPI AG, 2019)
The purpose of this pilot study was to explore the impact of pharmacist-provided recommendations to general practitioners (GPs) of patients living in assisted living facilities (ALFs). A secondary objective of this study was to explore prescriber and ALF staff perceptions. This was a mixed-method, quasi experimental 1-group pre/post-test study with an explanatory qualitative arm using in-depth semi-structured interviews at five regional ALFs and one independent community pharmacy in East Tennessee. Residents older than 65 years of age, with confirmed diagnosis of Type II diabetes in the pharmacy’s medical record, taking anti-diabetic medication for at least 14 days and resident of affiliated ALF for at least past 30 days were enrolled. Phase 1 demonstrated a 35.1% (13/37 recommendations) acceptance rate of pharmacist recommendations. Phase 2 demonstrated a similar 31.3% acceptance rate of pharmacist recommendations (5/16 recommendations). The mean pre⁻post difference in average 30-day FBG was greater in the accepted group than the rejected recommendation group (−9.1 vs. −2.3 mg/dL). Pharmacist⁻GP collaboration in the ALF population was feasible and may improve the quality of patient care of these residents.